Utility of a multiple serum biomarker test to monitor remission status and relapse in dogs with lymphoma undergoing treatment with chemotherapy. (15th October 2014) - Alexandrakis, I.; Tuli, R.; Ractliffe, S. C.; Tappin, S. W.; Foale, R. D.; Roos, A.; Slater, K. J.
Abstract: A blinded retrospective study was conducted to investigate remission and recurrence of lymphoma in dogs receiving chemotherapy. The objective was to compare clinicians' assessment using palpation and cytology to the results of serum biochemical tests for haptoglobin (Hapt) and C‐reactive protein (C‐RP). These biochemical test results were combined using a diagnostic algorithm developed using data from 344 individual dogs. This multivariate approach, termed the canine lymphoma blood test (cLBT), was used to follow 57 dogs during and after treatment. cLBT of remission and recurrence compared well with clinicians' assessment and differentiated dogs in remission and those with recurring disease before appearance of lymphadenopathy ( P  < 0.001). The cLBT demonstrated prognostic potential based on pre‐treatment values on dogs with shorter survival times and on those achieving the lowest cLBT score during treatment that showed longer survival times. The test, therefore, demonstrates potential to assist in monitoring treatment of canine lymphoma.